Community Education Managing for Success. - American Association of School Administrators ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
An examination of several school systems across the country offering community education programs provided information for this report on successful management techniques and unique program ideas, featuring tips from experts and a number of "how-to" suggestions. Drawing particularly on the experiences of administrators with programs in Flint, Michigan; Charleston County, South Carolina; Brevard and Duval Counties, Florida; Jefferson County, Alabama; Roseville, Minnesota; and the Fort Frye School District in Ohio, the report discusses the concept of community education, reasons for offering community education programs, and problems in establishing programs. The roles assumed by the people involved, the levels of commitment required, and methods for encouraging community support and involvement are also treated. (PGD)
Availability: American Association of School Adminstrators, 1801 N. Moore St., Arlington, VA 22209 (Stock No. 021-00202; $9.95).
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: PO07060506.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advisory Committees; Citizen Participation; Community Centers; Community Cooperation; Community Education; Community Involvement; Community Services; Program Administration; Program Development; Program Implementation; School Community Relationship; Information Analyses; Guides, Non-Classroom.